Olfactory Bulb Signal Abnormality in Patients with COVID-19 Who Present with Neurologic Symptoms - Strauss, S.B.; Lantos, J.E.; Heier, L.A.; Shatzkes, D.R.; Phillips, C.D. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: Unique among the acute neurologic manifestations of Severe Acute Respiratory Syndrome coronavirus 2, the virus responsible for the coronavirus disease 2019 (COVID-19) pandemic, is chemosensory dysfunction (anosmia or dysgeusia), which can be seen in patients who are otherwise oligosymptomatic or even asymptomatic. The purpose of this study was to determine if there is imaging evidence of olfactory apparatus pathology in patients with COVID-19 and neurologic symptoms.MATERIALS AND METHODS: A retrospective case-control study compared the olfactory bulb and olfactory tract signal intensity on thin-section T2WI and postcontrast 3D T2 FLAIR images in patients with COVID-19 and neurologic symptoms, and age-matched controls imaged for olfactory dysfunction.RESULTS: There was a significant difference in normalized olfactory bulb T2 FLAIR signal intensity between the patients with COVID-19 and the controls with anosmia (P = .003). Four of 12 patients with COVID-19 demonstrated intraneural T2 signal hyperintensity on postcontrast 3D T2 FLAIR compared with none of the 12 patients among the controls with anosmia (P = .028).CONCLUSIONS: Olfactory bulb 3D T2 FLAIR signal intensity was greater in the patients with COVID-19 and neurologic symptoms compared with an age-matched control group with olfactory dysfunction, and this was qualitatively apparent in 4 of 12 patients with COVID-19. Analysis of these preliminary finding suggests that olfactory apparatus vulnerability to COVID-19 might be supported on conventional neuroimaging and may serve as a noninvasive biomarker of infection.COVID-19coronavirus disease 2019OBolfactory bulbSARS-CoV-2Severe Acute Respiratory Syndrome coronavirus 2